Middle School Education Quality Improvement Management - Abdul Adji; Hidayatulloh (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to get an overview of the efforts made by SMP Al-Islamiyah Putat Tanggulangin, Sidoarjo Regency in creating the ability to Survive in the midst of a wave of Government policies related to education as tangible evidence of the durability of an educational institution, on the other hand, the increasing number of competitive a new educational institution with an offer of various excellent programs. Creating private school institutions whose resources are provided with greater self-reliance and funds towards quality schools, alternative choices, or even referrals is not easy. This research is a qualitative research, using a phenomenological approach, as for how to obtain data by observation, interviews, and documentation, after the data is collected an analysis is carried out so as to produce the conclusion that this Al-Islamiyah Middle School is able to compete with other schools both local public and private schools. This school has implicitly implemented MPMBS and internal and external quality assurance efforts, as for what supports the survival of this school in the following ways; the number of students is stable or even increases every year, the infrastructure is adequate, public trust is still quite high, the school has an Islamic style even though it is a public school, is not affiliated with any particular community organization, the educational qualifications of the teachers are adequate and has the potential to teach effectively, the library runs smoothly. good, the morality of students is good, the cost is standard (affordable).